Effectiveness of “How to Write a Sentence” as Instructional Material to Improve the Writing Skills of Grade 6 Pupils - Apolonio, John Noah B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
As students’ progress in their studies, they must learn a variety of important skills. Among these is writing, which is undeniably one of the most important skills that every student must develop. However, writing has always been a major challenge for students learning English, particularly in elementary schools and for second language learners. This study determined the effectiveness of the instructional material "How to Write a Sentence" as an intervention to improve the writing skills and academic performance in English of Grade 6 students at a public elementary school in the Philippines. The one-group pretest-posttest design of the quasi-experimental research design was used in this study. A 50-item pretest and posttest were used to assess the participants' academic performance before and after the intervention was implemented. The mean, standard deviation, and paired-samples t-test were used to interpret the data. Results revealed that the use of the instructional material "How to Write a Sentence" was found to be an effective intervention in improving the writing skills and academic performance in English of Grade 6 students at a public elementary school in the Philippines. It is recommended that administrators should encourage teachers to collaborate in order to further enhance or improve the intervention material or to create other contextualized and localized learning materials suited to diverse learner types.